A CASE OF SIGMOID COLON CANCER PROLAPSE AS A RARE CAUSE OF ADULT ISCHEMIC INTUSSUSCEPTION - Djordjevic, Lidija; Lidija (Acta medicae Medianae, 2024)
Intussusception in adults is present with nonspecific symptoms, which can present diagnosis challenges. Herein, we describe a case with extremely painful sensitivity in anal prolapse of soft-tissue mass with hematoma, as well as signs of ischemia. An operation was performed, during which a large sigmoid intussusception with a 7-cm ulcerative tumor, being the leading point, was found. While the prolapsed intussusception per anus is most commonly associated with the rectum, the possibility of a sigmoid colonic prolapse should always be considered. In adults, intussusception of the large intestine is very often associated with colon cancer, and for this reason, it is necessary to undergo a surgical procedure in such patients.